2018
DOI: 10.1101/338194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise prediction of antibiotic resistance in Escherichia coli from full genome sequences

Abstract: The emergence of microbial antibiotic resistance is a global health threat. In clinical settings, the key to controlling spread of resistant strains is accurate and rapid detection. As traditional culture-based methods are time consuming, genetic approaches have recently been developed for this task. The diagnosis is typically made by measuring a few known determinants previously identified from whole genome sequencing, and thus is restricted to existing information on biological mechanisms. To overcome this l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Previously established findings regarding the significant challenge in providing accurate AMR predictions for P. aeruginosa have been affirmed by this work ( Aun et al., 2018 ). Likewise, we obtain high accuracy predictions for S. aureus and most antibiotic compounds in E. coli , reflecting earlier results obtained with approaches operating on curated sets of AMR markers instead of nucleotide k-mers ( Bradley et al., 2015 ; Moradigaravand et al., 2018 ). A notable example of the influence of the compound class on prediction accuracy is the consistently high performance of models for resistance to the fluoroquinolones ciprofloxacin (CIP) and levofloxacin (LEV), which is strongly determined by single nucleotide polymorphisms to the DNA gyrase gene gyrA and topoisomerase IV gene parC ( Jacoby, 2005 ).…”
Section: Discussionsupporting
confidence: 84%
“…Previously established findings regarding the significant challenge in providing accurate AMR predictions for P. aeruginosa have been affirmed by this work ( Aun et al., 2018 ). Likewise, we obtain high accuracy predictions for S. aureus and most antibiotic compounds in E. coli , reflecting earlier results obtained with approaches operating on curated sets of AMR markers instead of nucleotide k-mers ( Bradley et al., 2015 ; Moradigaravand et al., 2018 ). A notable example of the influence of the compound class on prediction accuracy is the consistently high performance of models for resistance to the fluoroquinolones ciprofloxacin (CIP) and levofloxacin (LEV), which is strongly determined by single nucleotide polymorphisms to the DNA gyrase gene gyrA and topoisomerase IV gene parC ( Jacoby, 2005 ).…”
Section: Discussionsupporting
confidence: 84%
“…Several recent studies describe in silico models for defining a genomic antibiogram and hopes are high that such technologies will complement the classic phenotypic methods [ 44 ]. Several studies have already demonstrated that in some cases, genomic antibiograms can be at least as good as phenotypic ones [ 30 , 45 47 ]. Contrary to our approach, these studies require extensive resistance marker databases.…”
Section: Discussionmentioning
confidence: 99%
“…For a large number of cases, these assumptions do not completely hold. Some studies have attempted to capture uncertainty in the genetic basis of resistance and reduce overfitting using a variety of statistical modeling and machine learning (ML) approaches ( Table 4 ) ( 45 , 78 85 ). For simplicity, we have placed them together here under the term “model-based” prediction.…”
Section: Model-based Antibiotic Resistance Predictionmentioning
confidence: 99%